Association of Bystander and First‐Responder Efforts and Outcomes According to Sex: Results From the North Carolina HeartRescue Statewide Quality Improvement Initiative. Issue 18 (18th September 2018) - Malta Hansen, Carolina; Kragholm, Kristian; Dupre, Matthew E.; Pearson, David A.; Tyson, Clark; Monk, Lisa; Rea, Thomas D.; Starks, Monique A.; Nelson, Darrell; Jollis, James G.; McNally, Bryan; Corbett, Claire M.; et al.
Abstract : Background: The Institute of Medicine has called for actions to understand and target sex‐related differences in care and outcomes for out‐of‐hospital cardiac arrest patients. We assessed changes in bystander and first‐responder interventions and outcomes for males versus females after statewide efforts to improve cardiac arrest care. Methods and Results: We identified out‐of‐hospital cardiac arrests from North Carolina (2010–2014) through the CARES (Cardiac Arrest Registry to Enhance Survival) registry. Outcomes for men versus women were examined through multivariable logistic regression analyses adjusted for (1) nonmodifiable factors (age, witnessed status, and initial heart rhythm) and (2) nonmodifiable plus modifiable factors (bystander cardiopulmonary resuscitation and defibrillation before emergency medical services), including interactions between sex and time (ie, year and year 2 ). Of 8100 patients, 38.1% were women. From 2010 to 2014, there was an increase in bystander cardiopulmonary resuscitation (men, 40.5%–50.6%; women, 35.3%–51.8%; P for each <0.0001) and in the combination of bystander cardiopulmonary resuscitation and first‐responder defibrillation (men, 15.8%–23.0%, P =0.007; women, 8.5%–23.7%, P =0.004). From 2010 to 2014, the unadjusted predicted probability of favorable neurologic outcome was higher and increased more for men (men, from 6.5% [95% confidence interval (CI), 5.1–8.0] to 9.7% [95% CI, 8.1–11.3]; women, from 6.3% [95% CI, 4.4–8.3] to 7.4% [95% CI, 5.5–9.3%]); while adjusted for nonmodifiable factors, it was slightly higher but with a nonsignificant increase for women (from 9.2% [95% CI, 6.8–11.8] to 10.2% [95% CI, 8.0–12.5]; men, from 5.8% [95% CI, 4.6–7.0] to 8.4% [95% CI, 7.1–9.7]). Adding bystander cardiopulmonary resuscitation and defibrillation before EMS (modifiable factors) did not substantially change the results. Conclusions: Bystander and first‐responder interventions increased for men and women, but outcomes improved significantly only for men. Additional strategies may be necessary to improve survival among female cardiac arrest patients.